Flatform Konseling Virtual ; Wujud Trasformasi Edukasi Terapeutik di Fasilitas Pelayanan Kesehatan - Taufik Hidayat; Anita Ariani; Nadzmi Akbar; Amrullah Amrullah (Al-Hiwar Jurnal Ilmu dan Teknik Dakwah, 2024)
Virtual counseling platforms provide the ability to maintain connectivity between healthcare providers and their patients. Patients can quickly receive diagnoses, enabling faster and more accurate responses to any changes in their health. This article explains the implementation and therapeutic education phases in healthcare facilities, particularly hospitals and community health centers, using virtual counseling platforms in telemedicine programs through a literature review and a descriptive approach. The policy for the therapeutic education process in virtual counseling platforms in healthcare facilities is divided into eight stages: assessing educational needs, medical record-keeping, disease diagnosis, medical equipment safety, pain management, diet and nutrition, rehabilitation techniques, and verification of understanding received. There are five therapeutic education topics: patient-oriented, disease-oriented, patient safety-oriented, rehabilitation material, and prevention material. In the virtual counseling platform, healthcare providers implement seventeen implementation actions in the therapeutic education process based on the educational phases. First, in the Pre-Interaction Phase, the implementation actions include self-evaluation, setting the stages of virtual counseling therapeutic education, and creating a written plan according to established SOPs. Second, in the Orientation Phase, implementation actions include introducing oneself, scheduling meetings (contracting), building rapport and trust, initiating a conversation, and closing the introduction session. Third, in the Working Phase, implementation actions involve increasing the patients' understanding and awareness of themselves, developing independence competencies, therapeutic actions, conducting health education, collaboration, delegation, and observation. Fourth, in the Termination Phase, implementation actions include making temporary terminations, final terminations with evaluation of actions, and contracting for follow-up care and treatment outcomes.